Rapid Buffer and Ligand Screening for Affinity Chromatography by Multiplexed Surface Plasmon Resonance Imaging. Issue 9 (10th August 2017) - Geuijen, Karin P. M.; van Wijk‐Basten, Daniëlle E. J. W.; Egging, David F.; Schasfoort, Richard B. M.; Eppink, Michel H.
Abstract : Protein purifications are often based on the principle of affinity chromatography, where the protein of interest selectively binds to an immobilized ligand. The development of affinity purification requires selecting proper wash and elution conditions. In recent years, miniaturization of the purification process is applied to speed up the development (e.g., microtiterplates, robocolumns). The application of surface plasmon resonance imaging (SPRi) as a tool to simultaneously screen many buffer conditions for wash and elution steps in an affinity‐based purification process is studied. Additionally, the protein A ligand stability after exposure to harsh cleaning conditions often limits the reuse of resins and is determined at lab scale. The SPRi technology to screen ligand life‐time with respect to alkali stability is used. It is also demonstrated that SPRi can successfully be applied in screening experiments for process developments in a miniaturized approach. The amount of resin, protein and buffer in these studies is reduced 30–300‐fold compared to 1 mL column scale, and approximately 10–1000‐fold compared to filter plate experiments. The overall development time can be decreased from several months towards days. The multiplexed SPRi can be applied in screening affinity chromatography conditions in early stage development for ligand development and recombinant protein production. Abstract : Protein purification process development is often performed at small scale to reduce material consumption and development time. High‐throughput development is generally performed using small scale columns or filter plates to define the most optimal purification conditions for a new process or protein. Further miniaturization and higher throughput can be achieved by performing screening experiments on a multiplexed surface plasmon resonance platform for development of affinity chromatography processes, demonstrated here using protein A−IgG interactions as a model system.